In House Training (IHT): Upaya Meningkatkan Kompetensi Guru SMPN 3 Lingsar dalam Membuat dan Menggunakan Media Power Point - Dedi Setiawan (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
This study aims to improve the ability of teachers to create and use PowerPoint media in learning, increase the competence of prospective principals and improve the quality of student learning. The type of research used is school action research. The subjects used in this study were 10 teachers and 33 students in class IX-A at SMPN 3 Lingsar. The results showed that In House Training (IHT) in an effort to improve the competence of SMPN 3 Lingsar teachers in making and using PowerPoint media in learning was able to increase teacher competence in making and using PowerPoint media, it was seen from Cycle I of 74.98% increased to 96.90% in Cycle II, Implementation of Competency Improvement Plan for Principal Candidates in Cycle I was 94.11% increased to 98.54% in Cycle II, Competence of Principal Candidates based on AKPK from Cycle I increased to 97.86 % in Cycle II, the learning competence of students in Cycle I was 77.48% increased to 88.75% in Cycle II and Student Wellbeing Achievement from Cycle I was 80.83% increased to 88.75% in Cycle II. Based on these data, it can be concluded that In House Training (IHT) PowerPoint media can improve the competence of teachers, prospective principals, and students